2017
DOI: 10.1177/0961000617726123
|View full text |Cite
|
Sign up to set email alerts
|

Modelling digital library success using the DeLone and McLean information system success model

Abstract: This is an exploratory study to model the determinants of actual use of a digital library system. To do so, a research model was developed using Delone and McLean’s information system success model and explained as an empirical study. Data were collected from 978 respondents using a structured questionnaire from four different universities of Malaysia. The findings showed that the quality factors of digital library systems have a strong influence on satisfaction, behavioral intention, and variance in actual us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 79 publications
(79 reference statements)
10
88
1
12
Order By: Relevance
“…The D&M ISS model argues that information quality has a significant influence on technology use and user satisfaction. This assumption was confirmed in this study for both the SNS and LMS models, supporting the findings of previous research (Dong et al, 2014;Alzahrani, Mahmud, Ramayah, & Alfarraj, 2017;Ramirez-Correa et al, 2017;Yakubu & Dasuki, 2018). This means that the students found the quality of information obtained using the SNS and LMS was complete, relevant, and accurate.…”
Section: Discussionsupporting
confidence: 91%
“…The D&M ISS model argues that information quality has a significant influence on technology use and user satisfaction. This assumption was confirmed in this study for both the SNS and LMS models, supporting the findings of previous research (Dong et al, 2014;Alzahrani, Mahmud, Ramayah, & Alfarraj, 2017;Ramirez-Correa et al, 2017;Yakubu & Dasuki, 2018). This means that the students found the quality of information obtained using the SNS and LMS was complete, relevant, and accurate.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with the research of [36]; [5] and [35]. But the results of this study are not consistent with the research of [37] because there needs to be a system innovation appropriate with needs of users.…”
Section: ) System Quality Behavioral Intention and Use Of Behaviorcontrasting
confidence: 44%
“…DeLone and McLean's (1992) IS success model has been successfully applied to study usage of information in various contexts (e.g. Alzahrani, Mahmud, Ramayah, Alfarraj, and Alalwan, 2017;Tam and Oliveira, 2017;Wang and Liao, 2008;Wei et al, 2017). In a metaanalytic assessment of the DeLone and McLean IS success model, Petter and Mclean (2009) concluded that: "...the majority of the relationships posited in the updated D&M IS success model were supported.…”
Section: Theoretical Foundationmentioning
confidence: 99%